Analisis Determinan Perilaku Keuangan Mahasiswa Melalui Financial Technology, Literasi Keuangan, Gaya Hidup, Dan Pendapatan Orang Tua - Sumari, Jenita; Parastri, Desirianingsih H; Shaleyanty, Eka P.C (ACE: Accounting Research Journal, 2025)
ABSTRACT This study examines the influence of financial technology usage, lifestyle, financial literacy, and parental income on the financial behavior of students at the Faculty of Economics and Business, University of Papua. Employing a quantitative approach, data were gathered from 302 students using purposive sampling and analyzed with multiple linear regression. The findings reveal that financial technology, financial literacy, and parental income positively and significantly affect students’ financial behavior, while lifestyle has no significant impact. These results highlight the importance of technology adoption and financial knowledge in fostering prudent financial behavior among students, especially in regions with limited economic resources and financial access. The study’s scope is limited to one faculty and does not include mediating variables such as financial attitude or self-control. Future research should broaden the sample, incorporate qualitative methods, and consider additional variables like financial attitude and planning. The implications suggest that educational institutions and fintech providers should collaborate to enhance financial literacy programs and develop more responsive financial products tailored to students’ needs. Keywords: financial technology; financial literacy; parental income; student financial behavior; higher education